A CORPUS-BASED ANALYSIS OF VERBS IN NEWS SECTION OF THE JAKARTA POST: HOW FREQUENCY IS RELATED TO TEXT CHARACTERISTICS - Ikmi Nur Oktavianti; Novi Retno Ardianti (JOALL (Journal of Applied Linguistics and Literature), 2019)
Verb is one of the most important word classes in linguistic construction due to its prominent role and dynamic nature. Interestingly, the use of verbs in different linguistic contexts might be various because the context can limit or allow certain verbs to occur more frequently than other verbs. It is compelling to study further the use of verbs in a particular linguistic context. This paper thus aims at examining the use of verbs in news section in The Jakarta Post to figure out the frequency of verbs and how it relates to the characteristics of news text. This study compiled The Jakarta Post corpus comprising news articles belong to the category of hard news from October to December 2018 with total size of 21.682 words. The verb types used in this study refer to those compiled by Scheibmann (combining Halliday’s verb taxonomy and Dixon’s verb types). Based on the analysis, it is obvious that verbal type is the most frequent verb type, followed by material and existential. As for the least frequent ones, there are corporeal and perception/relational types. It is plausible that verbal type occupies the most frequent position because the nature of news text is to deliver information and thus it needs to use verbal verbs quite often. Likewise, material verb is frequent because it states concrete action and existential verb denotes existence; both are vital in constructing news text. Meanwhile, corporeal and perception/relational types are least frequent because corporeal deals with bodily gestures actions and perception/relational shows subjectivity. Both verb types are rather insignificant concepts in news writing. Based on the results of analysis, it is obvious that there is a firm relation between frequency of verbs used in news text and the characteristics of the text: linguistic units that are not in accordance with the function of the text are not really needed and thus infrequently used.